2017
DOI: 10.1111/micc.12385
|View full text |Cite
|
Sign up to set email alerts
|

Rosa rugosa flavonoids alleviate myocardial ischemia reperfusion injury in mice by suppressing JNK and p38 MAPK

Abstract: Objective: Although Rosa rugosa has been applied for preventing coronary artery disease, the pharmacological mechanism is little explored. In this study, the effects and mechanisms of Rosa rugosa flavonoids (RRF) on myocardial ischemia reperfusion injury (MIRI) were investigated. Methods:Mice were pretreated by intragastric administration of 600 mg/kg RRF for 7 days. Then MIRI was induced by 45 minutes coronary artery ligation and 3 hours reperfusion. Myocardial infarct size (MIS) and histopathology, activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…ERK is activated by various growth factors, controls cell growth and promotes cellular survival in IR injury [42] . In contrast, p38 and JNK are activated by stress conditions, leading to the cellular apoptosis via multiple mechanisms [43] . Several studies have argued that the intensity and balance of MAPK activities are important determinants of the cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…ERK is activated by various growth factors, controls cell growth and promotes cellular survival in IR injury [42] . In contrast, p38 and JNK are activated by stress conditions, leading to the cellular apoptosis via multiple mechanisms [43] . Several studies have argued that the intensity and balance of MAPK activities are important determinants of the cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…Zhaoqi H. et al used c57BL6/J mice to establish a MIRI model to study the protective effect of microRNA-374a targeting the MAPK6 pathway [18]. Xuehui Z. use ICR mice to establish a MIRI model to study inhibition of the JNK and p38 MAPK by Rosa rugosa avonoids to reduce myocardial ischemia-reperfusion injury [19]. Yang D. et al developed an SD rat MIRI model by ligating LAD for 1 h and subsequent reperfusion for 24 h [20].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical evidence has shown that myocardial ischemia is a potent stimulant of p38 activation, which might increase the production of inflammatory cytokines and accelerate the rate of infarction/death (9). A previous study has demonstrated that the p38-MAPK signaling pathway inhibitor SB203580 significantly repressed MI/R injury through its anti-inflammatory, anti-oxidative and anti-apoptosis effects (47). In the present experiments, the small-molecule compound VCP979 inhibited the MI/R injury-triggered activation of the p38-MAPK signaling pathway in murine models.…”
Section: Discussionmentioning
confidence: 99%